Psychological Demands of International Rugby Sevens and Well-Being Needs of Elite South African Players - Kruyt, Ninette; Grobbelaar, Heinrich (Frontiers in Psychology, 2019)
Rugby sevens was included in the 2016 Olympic Games, with South Africa’s Blitzboks winning bronze. They also won the 2016/17 and 2017/18 World Rugby Sevens Series. Whilst peak performance is paramount at the elite level there is a growing responsibility to address player well-being and off-the-field player needs. This study explored the psychological demands of international rugby sevens and the well-being needs of elite players. Twenty professional players (age range: 21-33 years) participated in semi-structured interviews. Qualitative content analysis yielded five categories of psychological demands: 1) tournament structure, 2) resilience, 3) cope with physicality, 4) perform when fatigued, and 5) perform under pressure. The prevailing team culture included: 1) team cohesion, 2) clear objectives, 3) work ethic, 4) team values, 5) happy environment, 6) relationships with coaching staff, and 7) faith. Various psychological skills [1) goal-directed behavior, 2) compartmentalization, 3) deal with anxiety, 4) motivation, 5) imagery, and 6) self-confidence)] and mental strategies [1) coping, 2) “back-to-zero”, 3) creativity, and 4) cognitive triggers] utilized by the players are discussed. Their general well-being and individual needs were: 1) physical needs, 2) financial concerns/ needs, 3) preparation for life after rugby career, and 4) general well-being and mental health. This information could be useful to develop an integrated sport psychological and well-being program aimed at improving performance and facilitating psychological well-being both during and after retirement from elite sport.